Characterization of flow transport within pore spaces of an open-work gravel bed - Lakshmanan, Susithra; Pender, Gareth; Haynes, Heather; Holmes, William (International Journal of Engineering and Technology, 2014)
Analysis of the flow dynamics within the near-bed and sub-surface regions of river bed sediment is critical in understanding fluid exchange and related chemical transfer/reactions. The knowledge in above is limited as these regions are difficult to measure using traditional instrumentation methods. In this paper, we tried the use of Magnetic Resonance Imaging (MRI) technique to non-invasively image flow dynamics of simulated river bed. We developed a bespoke MRI-compatible open-channel flume in order to acquire real-time flow images from within the MRI bore and used contrast agent (Gd-DTPA) as a tracer through an immobile, porous gravel bed. Single MR Image slices along the flume length were obtained for analysis. The flow tracer images from within the sediment bed are calibrated from the output data in order to provide fully quantitative maps of tracer concentration at regular time intervals. These ‘white-box’ (i.e. data from within the porous bed) tracer profiles were evaluated with the CXTFIT computer package to estimate the transport parameters. The intention was both, to illustrate the appropriateness of MRI for flow-sediment research and to analyse the relationship between tracer dispersion and gravel framework structure. Keywords: Porous Gravel Bed, Magnetic Resonance Imaging, Tracer Transport, CXTFIT.